Etika Bisnis dalam Jual Beli Grosir Daster Batik di Pasar Johar Semarang - Adinda Risqiana Dewi Maulana; M. Taufiq Abadi (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study uses a qualitative approach to examine business ethics in the practice of buying and selling wholesale batik negligee at Pasar Johar Semarang. Primary and secondary data obtained through observation, interviews, and documentation. Pasar Johar Semarang is a traditional market which is famous for its lively buying and selling activities. In the practice of buying and selling wholesale, there are patterns that are commonly found, including competition between sellers, stock management, systems for returning or exchanging goods, and special agreements between sellers and buyers. This practice reflects the application of Islamic business ethical values ​​such as fairness, social responsibility, and honesty. The results of the study show that in Pasar Johar Semarang, the principle of mutual benefit is upheld in buying and selling activities. The importance of the principles of fairness and balance in buying and selling is also recognized. Even though there are risks and abuses in the system of returns or khiyar, the practice is still in accordance with the principles of Islamic law. This study provides an in-depth understanding of the practice of buying and selling wholesale batik negligee and the influence of business ethics in transactions conducted at Pasar Johar Semarang.